Introducing Difficulty-Levels in Pronunciation Learning - Cabral, Joao; Zahra, Amalia; Carson-Berndsen, Julie; Kane, Mark (International Speech Communication Association (ISCA), 2011)
This paper presents a method to introduce the notion of a student selected difficulty level for the task of pronunciation learning of a second language. Three difficulty levels, novice, acceptable and native, are constructed using a tri-/bi- and unigram language model each using a specific set of broad phonetic groups determined using underspecification. The evaluation of the experiment is based on a target language of American English where Nigerian, Hungarian, Indonesian, Syrian, Pakistani and Portuguese students participate. The results show that the addition of difficulty levels returns specific mis-pronunciation information for a student indicating what pronunciation practice is required before they go to the next difficulty level.
International Speech Communication Association Special Interest Group on Speech and Language Technology in Education (SLaTE)
Keywords: Pronunciation learning; Broad phonetic groups; Creative Technologies; Computer Assisted Language Learning (CALL); SPEECH RECOGNITION